Effect of Diabetes on Survival after Resection of Pancreatic Adenocarcinoma. A Prospective, Observational Study. - Gianpaolo Balzano; Erica Dugnani; Alessandra Gandolfi; Marina Scavini; Valentina Pasquale; Francesca Aleotti; Daniela Liberati; Gaetano Di Terlizzi; Giovanna Petrella; Michele Reni; Claudio Doglioni; Emanuele Bosi; et al. (PLoS ONE, 2016)
To investigate the effect of diabetes mellitus (DM) on disease-free and overall post-resection survival of patients with pancreatic ductal adenocarcinoma (PDAC).Prospective observational study on patients admitted for pancreatic disease from January 2008 to October 2012. DM was classified as recent-onset (<48 months before PDAC diagnosis), longstanding (≥48 months before PDAC) or new onset (after surgery).Of 296 patients, 140 had a diagnosis of DM prior to surgery (26 longstanding, 99 recent-onset, 15 with unknown duration). Median follow-up time was 5.4 ± 0.22 years. Patients with recent onset DM had poorer postoperative survival than patients without DM: disease-free survival and overall survival were 1.14±0.13 years and 1.52±0.12 years in recent onset DM, versus 1.3±0.15 years and 1.87±0.15 years in non-diabetic patients (p = 0.013 and p = 0.025, respectively). Longstanding DM and postoperative new onset DM had no impact on prognosis. Compared to cases without DM, patients with recent onset DM were more likely to have residual disease after surgery and to develop liver metastases during follow-up. Multivariate analysis confirmed recent onset DM was independently associated with PDAC relapse (hazard ratio 1.45 [1.06-1.99]).Preoperative recent onset DM has an impact on survival after the resection of PDAC.